Classification of Pulse Waveforms Using Edit Distance with Real Penalty. (30th August 2010) - Zhang Zhang, Dongyu Dongyu; Zuo Zuo, Wangmeng Wangmeng; Zhang Zhang, David David; Zhang Zhang, Hongzhi Hongzhi; Li Li, Naimin Naimin
Abstract : Advances in sensor and signal processing techniques have provided effective tools for quantitative research in traditional Chinese pulse diagnosis (TCPD). Because of the inevitable intraclass variation of pulse patterns, the automatic classification of pulse waveforms has remained a difficult problem. In this paper, by referring to the edit distance with real penalty (ERP) and the recent progress in k -nearest neighbors (KNN) classifiers, we propose two novel ERP-based KNN classifiers. Taking advantage of the metric property of ERP, we first develop an ERP-induced inner product and a Gaussian ERP kernel, then embed them into difference-weighted KNN classifiers, and finally develop two novel classifiers for pulse waveform classification. The experimental results show that the proposed classifiers are effective for accurate classification of pulse waveform.